Analysis of Green Accounting, Corporate Performance, and Carbon Emissions Disclosure with Gender Diversity in the Board of Directors as a Moderating Variable - Julianto, Hery; Yunita , Khristina; Fahmi , Muhammad; Helmi, Syarif M; Dosinta, Nina Febriana (Sebatik, 2025)
This study aims to analyze the influence of green accounting, company performance, and carbon emission disclosure on firm value, with gender diversity on the board of directors as a moderating variable in consumer goods companies listed on the Indonesia Stock Exchange from 2020 to 2023. Employing a quantitative causal-comparative research design, secondary data were collected from annual reports, sustainability reports, and environmental performance rating documents (PROPER). Statistical analyses including descriptive statistics, classical assumption tests, multiple linear regression, and moderated regression analysis were conducted using SPSS 25. The results reveal that green accounting, company performance, and carbon emission disclosure have significant positive effects on firm value. Moreover, gender diversity on the board significantly moderates these relationships, though with varying effects: it weakens the positive impact of green accounting on firm value but strengthens the effects of company performance and carbon emission disclosure. These findings suggest that while environmental accounting practices and corporate performance are critical in enhancing firm value, the role of gender diversity introduces complex dynamics in corporate governance influencing sustainability outcomes.